2009
DOI: 10.1152/japplphysiol.91620.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lung transplant and volume reduction surgery on respiratory muscle function

Abstract: Lung transplantation and lung volume reduction surgery have opened a new therapeutic era for patients with advanced emphysema. In addition to providing impressive clinical benefits, they have helped us better understand how the chest wall and respiratory muscles adapt to chronic hyperinflation. This article reviews the effects of these procedures on respiratory muscle and chest wall function. Inspiratory (including diaphragm) and expiratory muscle strength are often close to normal after unilateral and bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In the present study, sniff Pdi did not differ between LTRs and controls, and values in LTRs were even higher than previously reported [14]. This finding is not inconsistent with diaphragm dysfunction in LTR: while lung transplantation, especially if bilateral, leads to reduced lung volume and enhanced inflatability of the lung during the sniff maneuver [14,37], inspiratory strength may be shifted to near-normal values by compensatory activation of other inspiratory muscles.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, sniff Pdi did not differ between LTRs and controls, and values in LTRs were even higher than previously reported [14]. This finding is not inconsistent with diaphragm dysfunction in LTR: while lung transplantation, especially if bilateral, leads to reduced lung volume and enhanced inflatability of the lung during the sniff maneuver [14,37], inspiratory strength may be shifted to near-normal values by compensatory activation of other inspiratory muscles.…”
Section: Discussionsupporting
confidence: 53%
“…Several factors contributing to the reduced exercise performance have been discussed, including cardiovascular and muscular deconditioning due to inactivity34 and intake of immunosuppressive agents 35. Additionally, it has been reported that patients transplanted for diseases that produce chronic hyperinflation, such as CF and emphysema, may have preoperative structural changes in rib cage shape that persist in part after transplantation and lead to persistent increases in functional residual capacity and residual volume 36. These alterations, when still present after transplantation, might contribute to decreased exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether diaphragm fiber lengths physically shorten by deletion of sarcomeres in series in chronically hyperinflated humans has never been clearly established, in part because of the difficulty in accurately measuring sarcomere length in vivo, at FRC. It is a critically important problem to understand because of the obvious implications for lung volume reduction surgery, as discussed in the accompanying review in this series (19). Some studies have measured human diaphragm length using computed tomography, coupled with three-dimensional modeling, e.g., Ref.…”
Section: Length Plasticitymentioning
confidence: 99%